Asuhan Keperawatan pada Ny.T dengan Diabetes Mellitus Di Ruang Catelya Panti Sosial Tresna Werdha Budi Mulia 1 - Jihan Rahma Fauzia, (2023)
Diabetes Mellitus (DM) is a condition characterized by high blood glucose (hyperglycemia) caused by inadequate insulin secretion, defective insulin action or both. This research was conducted to analyze the application of nursing assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. Research Method: This research uses a descriptive method with a case study approach. Research Results: The results of this study found that the main nursing problem is the instability of blood glucose levels associates with insulin retention. The main nursing action applied is to do diabetic foot exercises. Nursing evaluation is resolved with the goals and outcome criteria set. Conclusion: The application of nursing care to Ny.T with Diabetes Mellitus (DM) achieves the expected results due to good cooperation between nurses, patients, and nursing staff.